Upaya Administratif Sengketa Antara Pegawai Negeri Sipil dengan Pemerintahan Provinsi Kepulauan Bangka Belitung - Fitri, Lezi; Manik, Jeanne Darc Noviayanti; Rosdiana, Ita (PROGRESIF: Jurnal Hukum, 2023)
Stages of administrative dispute resolution as regulated in Law No. 30 of 2014 concerning Government Administration, article 58 paragraph (6) bring about changes in the state administrative justice system in Indonesia, which are related to administrative efforts. This study aims to analyze administrative efforts that should be in line with what is stated in Supreme Court Regulation No. 6 of 2018 which discusses guidelines for resolving government administrative disputes after taking administrative measures with Law No. 51 of 2009 Second Amendment to Law no. 5 of 1986. In practice, there are several problems related between object of dispute and administrative efforts, first: whether administrative measures must be taken first before filing a claim for a state administrative dispute to the State Administrative Court, second, whether there are legal consequences if no administrative efforts are carried out by the plaintiff, third, whether If a difference is made in the deadline for filing a lawsuit, administrative efforts can increase the effectiveness of the ongoing legal process. Systematically this research uses a normative juridical approach. This research will obtain formulations of norms that can provide effective legal protection for the parties concerned in matters of state administrative disputes and analyze the effectiveness of applying different time limits in administrative efforts.